Menikmati Secangkir Teh Nasgithel Rasa Yogyakarta - Rujiyanto, Rujiyanto (Bina Nusantara University, 2013)
Enjoying the art exhibition is like enjoying a cup of hot sweet tea in the afternoon. There are mixed feelings that we enjoy when walking by the spaces and searching for the meaning of artworks. Exhibition